El grado cero del dibujo (2018)
Traditionally, every drawing consecrates a meaning, a signal of its origin or its destiny which is never exposed. This way of understanding the drawing, defines it along an operating system of marks in which the drawing is established as a language and so, isolates it from one of its fundamental components: the impulse. This system opens a gap between impulse and, its other basic component: the mark, because of the undeniable transition of the desire to the visible. The drawing is drifted away from the first mark, even when this is the closest to itself and to the impulse, even when the latter is always unreachable by means of the plasticity and the drawing always forces the mark to ornament itself. Despite the transmutation in its becoming, impulse and mark must work as a unit in such a way that the drawing can exist. In order to diminish the gap between them, one must turn to the drawing degree cero.